Variações semânticas em duas reinstanciações de Eveline e The Dead para o Português: um estudo baseado no sistema da valoração - Natalia Carvalho Cristofaro (2018)
This study examines the instantiation of APPRAISAL (MARTIN; WHITE, 2005) in literary texts written in English and the re-instantiation of APPRAISAL in translations into Brazilian Portuguese. The aim of this study is to investigate APPRAISAL in two short stories from the source text Dubliners, by James Joyce, and semantic variations in two translations. This study is based on the framework of the APPRAISAL system and follows Macken-Horariks (2003) discursive approach to the analysis of fictional texts in order to investigate evaluative patterns and metarelations. This discursive approach has not been previously carried out in descriptive translation studies. The methodology employed in this study consisted of two main steps. The first step involved the selection of excerpts from the source text and translated texts and encompassed two procedures. The first procedure comprised the selection of the short stories Eveline and The Dead from James Joyce's Dubliners (2001 [1914]) and two translations to Brazilian Portuguese by Hamilton Trevisan and José Roberto O'Shea. The second procedure involved the selection of excerpts corresponding to the three main stages of the narrative genre (Orientation, Complication and Resolution) from both short stories in the source text and the selection of the equivalent excerpts from the translated texts. The second main methodological step encompassed four procedures. The first procedure consisted in the insertion of excerpts in electronic spreadsheets, subsequent annotation according to the categories of the APPRAISAL system and division by phases of discourse. As a second procedure, percentage quantitative data relative to each excerpt were collected. The third procedure involved the alignment of the most frequent evaluative configurations to valueorientations (MARTIN; WHITE, 2005) and the identification of evaluative patterns and metarelations among the stages in what concerns the APPRAISAL instances. The final procedure consisted of the comparative analysis of evaluative configurations between source texts and translated texts in order to allow the identification of semantic variations in the reinstantiation of APPRAISAL. The results of this study indicate the occurrence of metarelations of contrast, confirmation and transformation in the analyzed excerpts. Evaluative patterns associated with the instantiation of syndromes of AFFECT, JUDGEMENT and APPRECIATIONwere identified, including a similar evaluative pattern at the end of the Resolution stage in both short stories. Semantic variations were identified in the three APPRAISAL subsystems, mainly in the coupling and commitment of GRADUATION, with effects on the re-instantiationof patterns and metarelations in the translated texts. The APPRAISAL analysis was found to be productive for the identification of narrative themes and semantic variations in reinstantiations.